Confirmation of prenatal diagnosis of cystic fibrosis by DNA typing of fetal tissues. Issue 2 (February 1988) - Curtis, A; Strain, L; Mennie, M; Brock, D J
Abstract : Tissues from eight fetuses, diagnosed on the basis of amniotic fluid microvillar enzyme assay as having cystic fibrosis, were conserved in frozen storage for up to three years. Adequate samples of undegraded DNA could be extracted from small intestine, lung, and liver. DNA typing, with restriction fragment length polymorphisms tightly linked to the cystic fibrosis gene, showed all eight diagnoses to have been correct. Determining the DNA genotype of fetal material can also be used to establish the linkage relationship between markers and the cystic fibrosis gene, and will permit subsequent first trimester prenatal diagnosis for couples who have no living affected child.